HUBUNGAN DAYA LEDAK OTOT TUNGKAI DAN KOORDINASI MATA DAN KAKI DENGAN KEMAMPUAN AKURASI SHOOTING SEPAKBOLA PADA TIM SSB RUMBAI PRATAMA - Normansyah Normansyah; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The aim of this research was to determine and prove the correlation between explosive power of the leg muscle and eye and foot coordination with the ability to accurately shoot football at the Rumbai Pratama SSB team. This type of research conducted in this research is to use a correlational research design. A sample of 22 people from the results of hypothesis research with saturated sampling techniques or sampling points. The results obtained did not correlate leg muscle strength with the accuracy of shooting in football matches in the Rumbai Pratama SSB Team, where the rcount (0.311) <of the rtable (0.433) at α = 0.05. But the pattern of the results of the second hypothesis there is a link between eye and foot coordination with the accuracy of shooting in football on the Rumbai Pratama SSB team, where the acquisition of rcount (0.862)> of the acquisition of rtable (0.433) at α = 0.05. In the third hypothesis there is a joint correlation between Leg Muscle Explosion Power and eye and foot coordination with the accuracy of shooting in football matches on the Rumbai Pratama SSB Team namely the acquisition of rhitung (0.865)> of the acquisition of rtable (0.433) on α = 0.05.Key Words: Explosive Power Of Leg Muscles, Eye And Foot Coordination, Shooting, Football